2011
DOI: 10.1182/asheducation-2011.1.310
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Therapy of Advanced Hodgkin Lymphoma

Abstract: Advanced-stage Hodgkin lymphoma (HL) has become a curable disease in the majority of patients. Research during the last decade has challenged chemotherapy with Adriamycin, bleomycin, vinblastine, dacarbazine (ABVD) as the standard of care and debates continue regarding the role of radiation therapy (RT) in this patient population. The incorporation of interim positron emission tomography (PET) imaging and, recently, further characterization of HL on cellular and molecular levels are emerging as tools for treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 50 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…The authors concluded that an early switch from ABVD to escBEACOPP could be done safely in PET2-positive patients [14]. Currently, additional studies using similar approaches are still recruiting patients [15]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that an early switch from ABVD to escBEACOPP could be done safely in PET2-positive patients [14]. Currently, additional studies using similar approaches are still recruiting patients [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Current ongoing prospective trials, which are still recruiting patients and employ risk-adapted strategies based on interim-PET activity [15], will probably provide new guidelines for the treatment of patients with advanced-stage HL.…”
Section: Discussionmentioning
confidence: 99%
“…Stage I–II patients are treated with chemotherapy, mainly ABVD, followed by involved field radiotherapy [5]. In stages III–IV, combination chemotherapy followed by consolidation radiotherapy in selected patients is the standard treatment, with three regimens: ABVD, escalated BEACOPP (bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, and prednisone) and STANFORD V (doxorubicin, vinblastine, mechlorethamine, vincristine, bleomycin, etoposide, and prednisone) [6]. While the majority of patients will be cured, treatment-related toxicities are often a cause of late mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Combination chemotherapy with or without radiation therapy results in long-term DFS and OS for about 80% of newly diagnosed patients with HL. [192] As in NHL autologous HCT is well established for the treatment of disease. [193] An approach to minimize relapse after autologous HCT for high-risk patients using the anti-CD30 antibody (brentuximab) conjugated to an anti-tubulin drug (vedotin) [SGN-35] [194] is currently being studied in a randomized phase III placebo-controlled trial as maintenance therapy following autologous HCT.…”
Section: Hodgkin Lymphomamentioning
confidence: 99%